UNRAVELING QUALITATIVE RESEARCH: BREAKING BARRIERS? - Handoko, Liza; Wuisan, Dewi; Meilani, Yohana; Sitompul, Thomson; Soetardjo, Mulyadi (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
This research aims to assist the researchers at Surya Nusantara Adventist College in gaining knowledge about qualitative research methods. The goal is to encourage respondents to conduct research using qualitative approaches in their respective fields of expertise. The workshop covered the following topics: What is qualitative research methodology, and how does it differ from quantitative methodology? What are the strengths and weaknesses of qualitative research, and how can one effectively conduct qualitative research (tips)? Prior to the workshop, the respondents admitted to having difficulty with qualitative research due to a lack of understanding. However, after the workshop, the respondents reported a better understanding of qualitative research concepts and felt motivated to consider qualitative research as an alternative method. 75% of participants stated that the material presented met their needs, and 81% said that it broadened their insights. They expressed motivation to apply qualitative research in their future projects.